At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Solution: Here, the given equations are,
[tex]: \implies8x+5y=2...(i)\:and\:y-2=0...(ii)[/tex]
From equation,(ii); y-2=0
[tex] \therefore \: y = 2.........(iii)[/tex]
Substituting the value of y from equation (iii) to equation (i),we get
[tex]: \implies{8x + 5y = 2}[/tex]
[tex]: \implies{8x + 5(2) = 2}[/tex]
[tex]: \implies{8x = 2 - 10}[/tex]
[tex]: \implies{8x = - 8}[/tex]
[tex]: \implies{x = - 1}[/tex]
[tex] \therefore \: x = - 1[/tex]
Thus, x= -1 and y= 2 is the solution.
- Checking at (-1,2)
8x+5y=2...(i) y-2=0...(ii)
8(-1)+5(2)=2 2-2=0
2=2(True) 0=0(True)
Answer: x = -1, y = 2
Step-by-Step Explanation:
=> 8x + 5y = 2 (Eq. 1)
=> y - 2 = 0 (Eq. 2)
We can Solve Eq. 2 :-
y - 2 = 0
=> y = 2
Substitute value of ‘y’ in Eq. 1 :-
8x + 5y = 2
8x + 5(2) = 2
8x + 10 = 2
8x = 2 - 10
8x = -8
x = -8/8
=> x = -1
Therefore; x = -1, y = 2
Step-by-Step Explanation:
=> 8x + 5y = 2 (Eq. 1)
=> y - 2 = 0 (Eq. 2)
We can Solve Eq. 2 :-
y - 2 = 0
=> y = 2
Substitute value of ‘y’ in Eq. 1 :-
8x + 5y = 2
8x + 5(2) = 2
8x + 10 = 2
8x = 2 - 10
8x = -8
x = -8/8
=> x = -1
Therefore; x = -1, y = 2
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.